Development of mountain domestic tourism close to the major urban areas of Nepal: South side of the Annapurna Massif and Helambu - Pierre Dérioz; Pranil Upadhayaya; Philippe Bachimon; Maud Loireau (Via@)
The tourist system which started to grow up around trekking in the Himalayan region of Nepal in the 1970s and 1980s is now changing due to growing demand, and a greater diversity of customers and practices. Firstly, these developments are described in two different sectors (the south side of the Annapurna massif and Helambu) which have received large numbers of visitors for many years and are both located close to two of the country’s cities (Kathmandu and Pokhara), with improved links via new roads providing better access to mountain valleys. Based on interviews and observation in the field, this research then focuses in particular on the recent and little-documented surge in domestic tourism which can also be observed in these mountain areas. In the absence of statistical data, it attempts to assess the scope of this tourism, to define its practices, and to present some initial findings on the cultural representations of mountains and the mountain recreational activities underpinning this domestic tourism.